2018
DOI: 10.3390/en11030688
|View full text |Cite
|
Sign up to set email alerts
|

A Fast-Transient Output Capacitor-Less Low-Dropout Regulator Using Active-Feedback and Current-Reuse Feedforward Compensation

Abstract: Abstract:In this paper, output capacitor-less low-dropout (LDO) regulator using active-feedback and current-reuse feedforward compensation (AFCFC) is presented. The open-loop transfer function was obtained using small-signal modeling. The stability of the proposed LDO was analyzed using pole-zero plots, and it was confirmed by simulations that the stability was ensured under the load current of 50 mA. The proposed compensation method increases gain-bandwidth product (GBW) and reduces the on-chip compensation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The OCL-LDO in [15] achieved both the wide bandwidth and the high DC gain by utilizing multiple feedback loops, at the expense of on-chip capacitance and quiescent current [16]. A fasttransient OCL-LDO using active-feedback and current-reuse feedforward compensation was presented in [17], but it also consumed a high quiescent current. Current efficiency, which refers to the ratio of load to input current, determines operational life in the world of portable electronics [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The OCL-LDO in [15] achieved both the wide bandwidth and the high DC gain by utilizing multiple feedback loops, at the expense of on-chip capacitance and quiescent current [16]. A fasttransient OCL-LDO using active-feedback and current-reuse feedforward compensation was presented in [17], but it also consumed a high quiescent current. Current efficiency, which refers to the ratio of load to input current, determines operational life in the world of portable electronics [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Applications for three-stage OTAs include headphone amplifiers, liquid crystal display (LCD) drivers, low-dropout (LDO) linear regulators and capacitive MEMS sensors [3,[10][11][12][13]. Some applications (for example, MEMS and active matrix LCD) require the amplifier to drive very large capacitive loads [14] and others (e.g., headphone drivers and MEMS sensors) need the amplifier to be able to drive a wide range of load capacitors over several orders of magnitude [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…Classical architectures relied on nested Miller compensation [2,7,[21][22][23][24][25][26][27] and it remains an attractive solution today [12,28]. Architectures that rely on reverse nested Miller provide an improved power efficiency [3,13,[29][30][31][32][33] but it has been recognized that nesting Miller capacitors leads to bulky and slow implementations and many architectures were devised to use a single Miller capacitor along with some ancillary compensation structures [4,11,14,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Some authors have also demonstrated compensation techniques that do not rely on a Miller capacitor at all [8,[49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, although multichip configurations are convenient for a sensor module design, the cost and size of the resulting modules increase. Thus, integration of the power management unit and passive components into a single sensor chip ( Figure 1b) is being actively pursued to reduce the module size and to increase market competitiveness [4][5][6][7][8][9]. The power management unit normally comprises a high-efficiency switching DC-DC converter and a linear low-dropout regulator.…”
Section: Introductionmentioning
confidence: 99%